Impact of ovarian transposition before pelvic irradiation on ovarian function among long‐term survivors of childhood Hodgkin lymphoma: A report from the St. Jude Lifetime Cohort Study. Issue 9 (11th May 2018) - Fernandez‐Pineda, Israel; Davidoff, Andrew M.; Lu, Lu; Rao, Bhaskar N.; Wilson, Carmen L.; Srivastava, D. Kumar; Klosky, James L.; Metzger, Monica L.; Krasin, Matthew J.; Ness, Kirsten K.; Pui, Ching‐Hon; Robison, Leslie L.; et al.
Abstract: Background: We reviewed the effect of ovarian transposition (OT) on ovarian function among long‐term survivors of childhood Hodgkin lymphoma (HL) treated with pelvic radiotherapy. Procedure: Female participants (age 18+ years) with HL in the St. Jude Lifetime Cohort Study (SJLIFE) were clinically evaluated for premature ovarian insufficiency (POI) 10 or more years after pelvic radiotherapy. Reproductive history including age at menopause and pregnancy/live births was available on all patients. Results: Of 127 eligible females with HL, 90 (80%) participated in SJLIFE, including 49 who underwent OT before pelvic radiotherapy. Median age at STLIFE evaluation was 38 years (range 25–60). In a multiple regression adjusted for age at diagnosis, pelvic radiotherapy doses > 1, 500 cGy (hazard ratio [HR] = 25.2, 95% confidence interval [CI] = 3.1–207.3; P = 0.0027) and cumulative cyclophosphamide equivalent doses of alkylating agents > 12, 000 mg/m 2 (HR = 11.2, 95% CI = 3.4–36.8; P < 0.0001) were significantly associated with POI. There was no significant association between OT and occurrence of POI (HR = 0.6, 95% CI = 0.2–1.9; P = 0.41). Conclusions: OT did not appear to modify risk of POI in this historic cohort of long‐term survivors of HL treated with gonadotoxic therapy. Modern fertility preservation modalities, such as mature oocyte cryopreservation, should be offered to at‐risk patients whenever feasible.